Self-Narratives and Subjectivation of Science Teachers - Marlécio Maknamara (Universidade de Lisboa, 2023)
(Auto)biographical investigations have demonstrated great promise to teacher education and when they advocate for themselves the ability to educate a teacher, it is because they have become central to disputes over the significance of teaching. The general objective was to investigate the subjectivation processes engendered in (auto)biographical research by science teachers. The methodology, inspired by Foucault, included reading, description and problematization of (auto)biographical narratives from three doctoral theses. The results show different discourses and discursive elements that demand and produce subject positions in Science teaching. The Science teacher who emerges from the narratives investigated here is a subject that is made up of multiple positions: auto-ethnographer, learner, conscious, hopeful, resilient, phoenix, converted, mediator, desirer of success, messianic, innovative researcher, autopoietic. We conclude that it is productive to focus on operative discourses in subjectivation processes. This exercise allows us to 'see and say' other connections between (auto)biographical research and teaching, particularly when it comes to research aimed at the renewal and reinvention of Science teaching.